Pemberian Suplemen Asam Amino Triptophan sebagai Upaya Menurunkan Kanibalisne Ikan Kerapu Macan (Epinephelus fuscoguttatus) - Agustina, Afiyanti; Saraswati, Tyas Rini (BULETIN ANATOMI DAN FISIOLOGI dh SELLULA, 2007)
The aim of this research was controlled the cannibalism of Epinephilus fuscoguttatus germ with tryptophan application in its feeding formulation. Tryptophan was treated for Epinephilus fuscoguttatus germ in the different concentration.Tryptophan is serotonin precursor which can decrease Epinephilus fuscoguttatusagressifity.This research was using Complete Randomize Design with 4 treatments and 3 replications. The treatments contained P0 (Control); 0,5%;1%;1,5% tryptophan amino acid which were added in its feed.The results of this experiment were indicated that application of 0,5% and 1% tryptophan amino acid in the food could decrease Epinephilus fuscoguttatus germ cannibalism.